Three-Year Follow-Up of Insomnia and Hypnotics after Controlled Internet Treatment for Insomnia - Blom, Kerstin (Sleep, 2016)
STUDY OBJECTIVES: To investigate the long-term effects of therapist-guided Internet-based insomnia treatment on insomnia severity and sleep medication use, compared with active control. METHODS: This study was an 8 week randomized controlled trial with follow-up posttreatment and at 6, 12, and 36 months, set at the Internet Psychiatry Clinic, Stockholm, Sweden. Participants were 148 media-recruited nondepressed adults with insomnia. Interventions were Guided Internet-based cognitive behavioral therapy for insomnia (ICBT-i) or active control treatment (ICBT-ctrl). Primary outcome was insomnia severity, measured with the Insomnia Severity Index. Secondary outcomes were sleep medication use and use of other treatments. RESULTS: The large pretreatment to posttreatment improvements in insomnia severity of the ICBT-i group were maintained during follow-up. ICBT-ctrl exhibited significantly less improvement posttreatment (between-Cohen d = 0.85), but after 12 and 36 months, there was no longer a significant difference. The within-group effect sizes from pretreatment to the 36-months follow-up were 1.6 (ICBT-i) and 1.7 (ICBT-ctrl), and 74% of the interviewed participants no longer had insomnia diagnosis after 36 mo. ICBT-ctrl used significantly more sleep medication (P = 0.017) and underwent significantly more other insomnia treatments (P < 0.001) during the follow-up period. CONCLUSIONS: The large improvements in the ICBT-i group were maintained after 36 months, corroborating that CBT for insomnia has long-term effects. After 36 months, the groups did not differ in insomnia severity, but ICBT-ctrl had used more sleep medication and undergone more other additional insomnia treatments during the follow-up period. CLINICAL TRIAL REGISTRATION: The trial was registered, together with a parallel trial, at Clinicaltrials.gov as “Internet-CBT for Insomnia” registration ID: NCT01256099. CITATION: Blom K, Jernelöv S, Rück C, Lindefors N, Kaldo V. Three-year follow-up of insomnia and hypnotics after controlled internet treatment for insomnia. SLEEP 2016;39(6):1267–1274.